2021
DOI: 10.3390/antiox10020252
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Protective Effects of Dendropachol, a New Bisbibenzyl Compound from Dendrobium pachyglossum, on Hydrogen Peroxide-Induced Oxidative Stress in HaCaT Keratinocytes

Abstract: Five compounds including a new bisbibenzyl named dendropachol (1) and four known compounds (2–5) comprising 4,5-dihydroxy-2,3-dimethoxy-9,10-dihydrophenanthrene (2), gigantol (3), moscatilin (4) and 4,5,4′-trihydroxy-3,3′-dimethoxybibenzyl (5) were isolated from a methanolic extract of Dendrobium pachyglossum (Orchidaceae). The chemical structures of the isolated compounds were characterized by spectroscopic methods. Dendropachol (1) was investigated for its protective effects on hydrogen peroxide (H2O2)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
(76 reference statements)
1
20
0
Order By: Relevance
“…Gigantol, a biphenolic compound found in Dendrobium species, has been reported exhibit numerous biological functions including antitumor effects in human liver and lung cancer, anti-in ammatory effects, and anti-oxidant effects. 23,27,29,35 Nevertheless, as far as we know, there is currently no research exploring the therapeutic effect of gigantol on OA chondrocytes dysfunction. In the present study, we demonstrated the therapeutic effect of gigantol on IL-1β-induced chondrocytes and OA mice model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gigantol, a biphenolic compound found in Dendrobium species, has been reported exhibit numerous biological functions including antitumor effects in human liver and lung cancer, anti-in ammatory effects, and anti-oxidant effects. 23,27,29,35 Nevertheless, as far as we know, there is currently no research exploring the therapeutic effect of gigantol on OA chondrocytes dysfunction. In the present study, we demonstrated the therapeutic effect of gigantol on IL-1β-induced chondrocytes and OA mice model.…”
Section: Discussionmentioning
confidence: 99%
“…22 Currently, a great number of studies implies that gigantol could exert multiple biological effects e.g., antioxidant, bene t of diabetic nephropathy, and restraint some kinds of cancers. [23][24][25] Moreover, previous evidences indicated that crude extracts from Dendrobium plants motivate the production of collagen in human dermal broblasts and inhibited MMP. 26 Deciga-Campos, M. et al suggested gigantol decreased carrageenan induced in ammation in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The 50% ethanolic extracts of Centella were dissolved with DMSO to produce a 1 mg/mL stock solutions. The treatment protocol was slightly modified from our previous in vitro experiments on skin cells 21 , 22 . To observe the preventive activities of Centella extracts against H 2 O 2 -induced cytotoxicity, BJ cells were pre-treated with the Centella extracts (final concentration, 15–60 µg/mL; 0.5% DMSO) for 24 h prior to H 2 O 2 treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Various assays are available to quantify antioxidant capacity and, from these, we chose DPPH and the potassium ferricyanide reducing power assay to evaluate the antioxidant potential of our samples, expressed as gallic acid equivalents (GAE) and ascorbic acid equivalents (AAE). These assays are used widely to determine the antioxidant properties of compounds as free radical scavengers or hydrogen donors [50], and the results are shown in (Table 4) The results of the DPPH assay revealed that the antioxidant capacity of the fruits ranged from 1.16 ± 0.02 to 239.7 ± 8.17 mg/g, expressed as GAE, and varied from 2.47 ± 0.05 to 124.4 ± 4.34 mg/g, expressed as AAE. Similarly, the reducing power assay recorded that, in comparison with all fruit samples, KKD-NT and KKD-WA showed the highest antioxidant properties, ranging from 6.65 ± 0.44 to 179.6 ± 5.35 mg GAE/g DW and from 14.08 ± 0.83 to 74.4 ± 2.06 mg AAE/g DW.…”
Section: Antioxidant Activity Of Plant Extracts: Dpph and Reducing Power Assaysmentioning
confidence: 99%